Pelatihan Pembuatan Produk Olahan Ikan Tenggiri (Dimsum Ikan) di Kulolu, Kelurahan Ganti, Kabupaten Donggala - Matius Paundanan; Iwana Grace; Nya Sulistari Palugu; Novitasari; Febrianti Prafita; Nur Fitra Ramadhani M. Hi Tone; Dita; Ayu Rizka; Muh Farhan A. Basjir; Lulun; Alia Amalia Risky; Muh. Alzumrah Kandouw (ABDI WIDYA NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The fish dimsum training program in Kulolu was implemented to improve the utilization of local fish resources and increase economic value through product diversification. The activity involved five community cadres and focused on processing mackerel into nutritious dimsum enriched with vegetables to enhance both sensory quality and nutritional content. The training was conducted through demonstrations followed by hands-on practice, covering ingredient preparation, mixing techniques, shaping, and steaming procedures. The results showed that participants successfully produced 25 pieces of fish dimsum, and all cadres expressed strong interest in developing fish-based home enterprises. These findings are consistent with previous studies demonstrating that training in fish processing can enhance skills, creativity, and entrepreneurial motivation among coastal communities. Overall, the program had a positive impact on participants’ capacities, strengthened local economic potential, and supported national efforts to increase fish consumption. Further program development through training in packaging, digital marketing, and product certification is recommended to expand market opportunities and ensure long-term sustainability.